2004
DOI: 10.1038/nmat1268
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic arrangement of BaCO3 nanocrystals into helices induced by a racemic block copolymer

Abstract: Morphosynthesis strategies inspired by biomineralization processes gives access to a wide range of fascinating and useful crystalline mesostructures. Biomimetic synthesis of inorganic materials with complex shapes can now be used to control the nucleation, tensorial growth, and alignment of inorganic crystals in a way previously not practicable. Double hydrophilic block copolymers (DHBCs) consisting of a hydrophilic block strongly interacting with inorganic minerals, and a non-interacting hydrophilic block, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
251
2
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 333 publications
(268 citation statements)
references
References 31 publications
6
251
2
9
Order By: Relevance
“…Strategies inspired by biomineralization have been explored as potential routes to controlling growth and self-assembly from the molecular level via tailored microenvironments, epitaxy and inorganic or organic additives (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Yet although these have produced some interesting spherical, spiral, leaf-like, and other shapes (25)(26)(27)(28)(29)(30)(31)(32), it is rather disappointing that the appearance of various forms in synthetic systems is often unexpected and the attempts to identify the mechanisms of their formation are generally assessed a posteriori..…”
mentioning
confidence: 99%
“…Strategies inspired by biomineralization have been explored as potential routes to controlling growth and self-assembly from the molecular level via tailored microenvironments, epitaxy and inorganic or organic additives (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Yet although these have produced some interesting spherical, spiral, leaf-like, and other shapes (25)(26)(27)(28)(29)(30)(31)(32), it is rather disappointing that the appearance of various forms in synthetic systems is often unexpected and the attempts to identify the mechanisms of their formation are generally assessed a posteriori..…”
mentioning
confidence: 99%
“…S7 in the ESM). According to attachment growth mechanism [21,44], it was suggested that the PAA molecules could selectively adsorb onto and protected the specific crystal planes of these small CaCO 3 particles, and then the other crystal planes with higher surface energy attached to each other to reduce the total surface energy and formed the initial nanowires, thereby providing specifically oriented seeds for the subsequent growth. Eventually, the polymer-adsorbed planes with low energy were left, e. g., {102…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the formation of anisotropic crystals can be achieved via tuning of the surface energy of crystal faces by changing the temperature and pH, or by adding specific molecules as modifiers [21][22][23][24][25]. An alternative method is to use prefabricated templates with designed shapes and surface functional groups [26][27][28][29].…”
mentioning
confidence: 99%
“…70) Zhou and O'Brien showed that particle-mediated crystallization leads to the formation of NH 4 TiOF 3 mesocrystals in the presence of a surfactant. 71), 72) As described in Section 1, nanometric crystals are arranged with the same crystallographic orientation in various CaCO 3 -based biominerals 20)22) (Fig. 1).…”
Section: Oriented Small Crystals With Organic Polymersmentioning
confidence: 99%